2010
DOI: 10.1111/j.1551-2916.2010.03604.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal‐like Mesoporous SrTiO3 Spheres with Enhanced Photocatalytic Performance

Abstract: Single-crystal-like mesoporous strontium titanate (SrTiO 3 ) submicrometer spheres with a wormhole-like structure were successfully synthesized by a facile hydrothermal method using polyvinyl alcohol (PVA) as additive. The microstructure was studied by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, selected area electron diffraction, and N 2 -physisorption techniques. The results demonstrated that the average pore size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Such an agglomeration process can also lead to the formation of pores. A similar crystal growth process was observed by Xu et al [17] With polyvinyl alcohol (PVA) as an additive, mesoporous SrTiO 3 with a wormholelike structure formed by an oriented aggregation of nanocrystals and also exhibited single-crystal-like character.…”
Section: Resultssupporting
confidence: 56%
“…Such an agglomeration process can also lead to the formation of pores. A similar crystal growth process was observed by Xu et al [17] With polyvinyl alcohol (PVA) as an additive, mesoporous SrTiO 3 with a wormholelike structure formed by an oriented aggregation of nanocrystals and also exhibited single-crystal-like character.…”
Section: Resultssupporting
confidence: 56%
“…According to IUPAC classification, the N 2 adsorptiondesorption curves of these three samples belong to the indicating that the samples are of macroporous structure [26]. As the pores in PC-polyHIPEs are 30∼100 m in diameter, over such material, the N 2 adsorption-desorption isothermal curve does not exactly reflect the pore situation.…”
Section: Characterization Of Srmentioning
confidence: 95%
“…CaTiO 3 has potential application in the fields of electricity [18], optics [19], catalysis [20] and biology [21]. On the other hand, it has reported that perovskite-type oxides, such as SrTiO 3 , could perform high photocatalytic properties [22]. So far, however, there have been a few studies on the photocatalytic properties of CaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%